1979
DOI: 10.1007/bf00234333
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and behaviour of neural crest cells of chick embryo in vitro

Abstract: Neural primordia of chick embryos were cultured for three days and the behaviour of migrating neural crest cells studied. Somite cells were used as a comparison. Crest cells were actively multipolar with narrow projections which extended and retracted rapidly, contrasting to the gradual extension of somite-cell lamelleae. On losing cell contact, somite cells were also more directionally persistent. The rate of displacement of isolated crest cells was particularly low when calculated over a long time base. Both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

1985
1985
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(37 citation statements)
references
References 58 publications
1
34
0
Order By: Relevance
“…However, studies of neural crest cells [Newgreen et al, 1979;Rovasio et al, 1983; Erickson, 1985bl demonstrate that NC cells are also contact inhibited.…”
Section: Introductionmentioning
confidence: 96%
“…However, studies of neural crest cells [Newgreen et al, 1979;Rovasio et al, 1983; Erickson, 1985bl demonstrate that NC cells are also contact inhibited.…”
Section: Introductionmentioning
confidence: 96%
“…(Noden, 1983). The need for individual neural crest cell pathfinding in this scenario is simplified if the neural tube controls cell exit points (Lumsden et al, 1991) such that cells diffuse laterally from high populations to low populations in segregated streams (LeDouarin, 1982;Newgreen et al, 1979;Rovasio et al, 1983). Studies in chick (Graham et al, 1993;Smith and Graham, 2001) and other amniotes (Knabe et al, 2004) show increased levels of cell death in specific rhombomeres, particularly r3 and r5.…”
Section: Introductionmentioning
confidence: 99%
“…Novel culture and imaging techniques, combined with Nomarski optics and labeling of premigratory neural crest cells, has allowed cell migratory behaviors to be visualized in tissue culture (Abercrombie, 1970;Bard and Hay, 1975;Erickson et al, 1980;Krull et al, 1995), in 2D and 3D gel substrates (Newgreen et al, 1979;Rovasio et al, 1983;Thomas and Yamada, 1992), in whole embryo culture (Spieth and Keller, 1984;Kulesa and Fraser, 1998), and in ovo (Kulesa and Fraser, 2000). Analyses of cell movements suggest the mechanisms that sculpt the pattern are more complex than would be expected from a purely directed diffusion model and may include cell-cell and cell-environment interactions in the form of chemotaxis, contact inhibition, contact guidance and haptotaxis.…”
Section: Introductionmentioning
confidence: 99%
“…Although the majority of ENCCs, which are presumably undifferentiated ENCCs, are often tapered in the direction of migration, they are multipolar with multiple short, transient filopodia that extend and retract from the cell body (Druckenbrod and Epstein, 2007). Other populations of migrating neural crest cells, including trunk and cranial neural crest cells in vitro (Newgreen et al, 1979), in explants (Kasemeier- Kulesa et al, 2006) and in vivo (Krull et al, 1995;Teddy and Kulesa, 2004;Kasemeier-Kulesa et al, 2005;McLennan and Kulesa, 2007;Rupp and Kulesa, 2007) have also been reported to be multipolar, and to extend and retract multiple filopodial extensions. Other migratory cells such as fibroblasts and neutro-phils also lack long-leading processes (Ridley et al, 2003).…”
Section: Mode Of Enteric Neuron Migrationmentioning
confidence: 99%